Israel in the making : stickers, stitches, and other critical practices - Salamon, Hagar (Indiana University Press, 2017)
The brilliant kaleidoscope of everyday creativity in Israel is thrown into relief in this study, which teases out the abiding national tensions and contradictions at work in the expressive acts of ordinary people. Hagar Salamon examines creativity in Israel's public sphere through the lively discourse of bumper stickers, which have become a potent medium for identity and commentary on national and religious issues. Exploring the more private expressive sphere of women's embroidery, she profiles a group of Jerusalem women who meet regularly and create "folk embroidery." Salamon also considers the significance of folk expressions at the intersections of the public and private that rework change and embrace transformation. Far ranging and insightful, Israel in the Making captures the complex creative essence of a nation state and vividly demonstrates how its citizens go about defining themselves, others, and their country every day.